2018
DOI: 10.4081/oncol.2018.373
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD markers in JAK2V617F positive myeloproliferative neoplasms: Prognostic significance

Abstract: Myeloproliferative neoplasms (MPNs) are clonal stem cell disorders characterized by the presence of JAK2V617F mutation. Thrombohemorrhagic as well as autoimmune or inflammatory phenomena are common clinical outcomes of these disorders. Recent studies have shown that abnormality in frequency and function of blood cells manifested by an alteration in CD markers’ expression patterns play a key role in these complications. So, there may be a relationship between CD markers’ expressions and prognosis of JAK2V617F p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…Interestingly, and as previously mentioned, the expression of CD177 ( PRV-1 ), a GPI-linked cell surface glycoprotein with a role in neutrophil activation, was increased in PV patients, and to a lesser extent in ET and PMF patients [ 64 , 65 ]. Indeed, higher CD177 expression was associated with an increased risk of thrombotic and bleeding complications due to increased circulating neutrophils [ 173 , 174 ]. For a complete and recent review on the role of neutrophils in thrombosis, we refer readers to the article by Ferrer-Marín and colleagues published in this special edition [ 175 ].…”
Section: Prognosismentioning
confidence: 99%
“…Interestingly, and as previously mentioned, the expression of CD177 ( PRV-1 ), a GPI-linked cell surface glycoprotein with a role in neutrophil activation, was increased in PV patients, and to a lesser extent in ET and PMF patients [ 64 , 65 ]. Indeed, higher CD177 expression was associated with an increased risk of thrombotic and bleeding complications due to increased circulating neutrophils [ 173 , 174 ]. For a complete and recent review on the role of neutrophils in thrombosis, we refer readers to the article by Ferrer-Marín and colleagues published in this special edition [ 175 ].…”
Section: Prognosismentioning
confidence: 99%
“…The phenotype of the involved cells, often characterized by the expression of surface CD markers, is another feature playing an essential role in the diagnosis and prognosis of hematological malignancies and solid tumors. 3 , 71 , 72 Although flow cytometry is a practical technique to analyze the expression levels of CD markers, genetic alterations (including SNPs) affecting expression patterns of CD markers may cause significant limitations in the classification and precise prognosis of hematological malignancies. 73-75 As an example, CD38 rs6449182 is a known polymorphism in CLL and it has been shown that patients carrying the GG genotype of this polymorphism have more aggressive disease.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%